O MUNDO NA SUA LÍNGUA : Rádio, internet e a BBC Brasil - Ferrão Neto, José Cardoso (2006)
This dissertation focuses on the trajectory of radio and its change from an analogical platform to the World Wide Web through the journalistic work in radio and internet of the BBC Brazilian Service. Its main purpose is to identify the transformation in production, circulation and consumption of information setting from different material supports that generate differential communication practices. The study has been developed taking into account the analysis on the oralized information processing regime as permanent in the analogical medium. After identifying some of the caracteristics of the internet, it verifies the transmutation of the medium within the new information space of the BBC Brasil website, multiple of languages and predominantly visual. The discussions presented here are based upon the theoretical references of the Toronto School of Communication, the Cultural History as well as on authors that are in tune with the comprehension of media as influential in the organization of both thought and culture. As methodological tool it presents transcriptions of radio programmes and descriptions of internet journalistic material. In conclusion, it highlightens the transformation of radio into audio, and therefore, from a medium into a language as radio goes from the analogical platform to the internet.